(untitled) (Chemical Engineering Research Bulletin, 2008)
In recent times Bangladesh celebrated 60 years of engineering education. The engineering education in Bangladesh has gone through different changes in its life span; however, there are plenty to improve to cope with the world trend of engineering. Industrial diversification, changes is socio-economic structures, and advancements of new sciences and technologies are forcing changes in engineering curriculum to keep the content compatible. This paper discusses some of the new ideas of engineering education practiced at different parts of the world. It also offers a review of the new approaches which can be applied in Bangladesh to make the engineering students more competitive and compatible, so that they can go through a lifelong learning process and confront the changes in engineering career. The overall goal of this article is to help improving the engineering education system in Bangladesh where students can develop themselves as independent and interdependent learners. Keywords: Integrated curriculum; Effective Teaching; Multidimensional competition; Student evaluation. DOI = 10.3329/cerb.v12i0.1492 Chemical Engineering Research Bulletin 12 (2008) 11-19